HUBUNGAN PERSEPSI IBU TENTANG COVID-19 DENGAN PEMENUHAN IMUNISASI DASAR LENGKAP DI PUSKESMAS MELATI KUALA KAPUAS - Muhsinin Muhsinin; Widia Widia; Isnawati Isnawati (LPPM Universitas Sari Mulia, 2021)
Background: Covid-19 causes high anxiety due to lack of knowledge, causing negative perceptions about covid-19. Perception can affect various aspects of life, one of which is immunization services. Where mothers are worried about bringing their children to health services to fulfill immunizations, while complete basic immunizations are important, even during the COVID-19 pandemic. Objective: This study aims to determine whether there is a relationship between mother's perception of COVID-19 and the fulfillment of complete basic immunization at the Melati Kuala Kapuas Health Center. Methods: This study used a correlation analytic design with a cross sectional approach. The population is mothers who have children aged 10-24 months at the Melati Kuala Kapuas Health Center as many as 23 mothers from January - February 2021. The research sample is all the population as samples. The instruments used are questionnaires and checklists using the Spearman Rank statistical test showing a p value of 0.005 and correlations coefficient = 0.564, the value is statistically significant (p < 0.05). Results: the study showed that there was a relationship between mother's perception of covid-19 and the fulfillment of complete basic immunization with a p value of 0.005 and correlations coefficient = 0.564 which means there is a moderate relationship. coefficient of determination R²(0.564)² = 0.32 =32%, which means that the mother's perception of covid-19 does not fully affect the fulfillment of complete basic immunization which can also be influenced by other factors. Where perception affects motivation, further researchers can examine other factors such as motivation Conclusion: There is a relationship between the mother's perception of covid-19 and the fulfillment of complete basic immunization at the Melati Health Center Kuala Kapuas